2022
DOI: 10.1126/sciadv.abl8920
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone sensitizes to ferroptosis by glucocorticoid receptor–induced dipeptidase-1 expression and glutathione depletion

Abstract: Dexamethasone is widely used as an immunosuppressive therapy and recently as COVID-19 treatment. Here, we demonstrate that dexamethasone sensitizes to ferroptosis, a form of iron-catalyzed necrosis, previously suggested to contribute to diseases such as acute kidney injury, myocardial infarction, and stroke, all of which are triggered by glutathione (GSH) depletion. GSH levels were significantly decreased by dexamethasone. Mechanistically, we identified that dexamethasone up-regulated the GSH metabolism regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Dexamethasone is reported to induce oxidative stress in skeletal muscles directly through binding to the glucocorticoid receptors and in pancreas, via deactivating PI3K/Akt/Nrf2 signaling pathways, and by inducing glucotoxicity of pancreatic islets [56] , [12] . Furthermore, a recent study showed that dexamethasone causes GSH depletion and induces ferroptosis in HT1080 cells in a glucocorticoid receptor dependent manner [2] . This may explain the effects of dexamethasone on the oxidative stress markers observed in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone is reported to induce oxidative stress in skeletal muscles directly through binding to the glucocorticoid receptors and in pancreas, via deactivating PI3K/Akt/Nrf2 signaling pathways, and by inducing glucotoxicity of pancreatic islets [56] , [12] . Furthermore, a recent study showed that dexamethasone causes GSH depletion and induces ferroptosis in HT1080 cells in a glucocorticoid receptor dependent manner [2] . This may explain the effects of dexamethasone on the oxidative stress markers observed in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoids are commonly utilized to treat a variety of disorders and recognized among the highly effective anti-inflammatory and immunosuppressive medications [1] . Dexamethasone belongs to this drug family and has recently been widely approved to treat the hospitalized, critically ill patients with coronavirus disease 2019 (COVID 19) [2] . However, glucocorticoids are linked to variety of adverse effects, such as new onset hyperglycemia in patients without diabetes mellitus (DM) history or hard-to-control hyperglycemia in people with DM.…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone (DXMS) can induce ferroptosis via P53/SLC7A11/GPX4 pathway in pre-osteoblast MC3T3-E1 cells and osteocyte MLOY4 cells in glucocorticoid-induced osteonecrosis ( 75 ). DXMS could reduce GSH by upregulating the expression of dipeptidase-1 (DPEP1) to increase the sensitivity to ferroptosis in HT1080 cells, and prednisolone was found to have a similar effect on ferroptosis-sensitivity-increasing effect in the study ( 74 ).…”
Section: Anti-rheumatic Drugs and Ferroptosismentioning
confidence: 92%
“…Several studies showed the potential of dexamethasone in modulating cell death, like regulated necrosis. Very recently, it has been proved that dexamethasone sensitizes erastin-induced ferroptosis via glutathione depletion [ 88 ]. Dexamethasone can also alleviate corneal alkali injuries by inhibiting the caspase-1/GSDMD-mediated pyroptotic signaling pathway [ 89 ].…”
Section: Immunological Potentials Of Regulated Necrosis-necroinflamma...mentioning
confidence: 99%